Is there a seasonal variation of survival after systemic chemotherapy for metastatic castration-resistant prostate cancer in a rural part of North Norway? - Nieder, Carsten; Dalhaug, Astrid; Haukland, Ellinor Christin (International Journal of Circumpolar Health, 2020)
The winter darkness or polar night induces endocrine and metabolic mechanisms, which might reduce the efficacy of cancer treatment and thus contribute to shorter survival. Moreover, season-and weather-related treatment delays and irregularities might also cause reduced efficacy of anti-cancer drugs. Therefore, this study evaluated the prognostic impact of timing of chemotherapy (start during winter darkness or outside of this season), in terms of overall survival, in patients with metastatic castration-resistant prostate cancer (MCRPC) who received oncology care at the Nordland hospital Bodø. The study included 111 patients treated with first-line docetaxel chemotherapy for MCRPC. Twenty patients (18%) started their treatment during winter darkness (arbitrarily defined as ±4 weeks around 21 December). In unadjusted univariate analysis, survival was shorter in this group (median 10.2 vs. 18.9 months, p = 0.055). However, not all baseline parameters were equally distributed between the two groups. In multivariable-adjusted Cox regression analysis accounting for several confounding variables, only one factor was statistically significant: pre-chemotherapy serum lactate dehydrogenase level (a surrogate marker of disease burden). Thus, the present results suggest that seasonal variation is not a major contributor to the diverging survival outcomes observed after docetaxel chemotherapy.